Reorientation of Approaches in Indonesian Customary Law Studies - Syamsudin, M.; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2017)
This paper is intended to describe some approaches in studying the Indonesian Adat Law. From the exposure is expected to provide various perspectives in studying the sides of Indonesian Adat Law that is used as the object of study of legal scholars today. The current issue of Indonesian Adat Law studies shows a very distressing and lagging state when compared to other legal studies such as Western Law. This situation indicates how Indonesian Adat Law will be left behind and will likely be alienated from the academic community in the future. The problem is allegedly caused by among others the lack and freezing of existing materials and the absence of unity of theme and orientation of study. This paper is intended as an effort to respond to the situation, namely the effort to provide direction and contribution of thought and further development of the study and teaching of customary law which is still ongoing in the faculties of law in general. This study is considered a study of doctrinal law with reference to secondary data. Secondary data collected were processed in a non-statistic, analyzed descriptively-qualitative, and presented narratively based on the topic of the problem studied. The results of this study indicate the need for the Indonesian Adat Law study approach within the framework of Indonesian national jurisprudence. The object of study of this approach is the idea of Adat Law that was born and started since the Indonesian Youth Congress in 1928, which in its development has spawned Pancasila and the 1945 Constitution as the basis and constitution of the independent Indonesian state. In this development Adat Law is essentially an escalation of the values and principles of local adat law into the values and principles of law that serve as the basis of the framework of Indonesian National Law. Therefore, it is necessary to approach Indonesian national jurisprudence in studying Adat Law.